Potential of Homestead Gardens to gain from global carbon markets to mitigate climate change in Cooch Behar, West Bengal - Pala, Nazir A.; Sarkar, Biplov C.; Gokhale, Yogesh; Abha Manohar, K.; Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2020)
Under Paris Agreement on Climate Change India has pledged for creating an additional 2.5 to 3 billion tons of CO2 equivalent by 2030. In this context strengthening of traditional agro-forestry and homestead garden systems practically spread all over India would be important for creating carbon sinks. International Compliance as well as Voluntary Carbon Markets provides excellent opportunities to incentivize the local communities by getting carbon credits from agro-forestry plantations. In the present study a total of 45 homestead gardens from three villages in Pundibari area of Cooch Behar-II Block ofdistrict Cooch Behar, West Bengal are selected for study purpose. The study demonstrates carbon sequestration potential and avoided deforestation due to the maintenance of the homestead gardens. These homestead gardens also play an important role in maintaining the diversity of the domesticated trees covering a total of 71 woody tree species belonging to 59 genera and 30 families. Total biomass of 7482.67 Mg is stored among all the woody species in all the 45 home gardens. The total live biomass has the potential to offset 507.94 Mg CO2e. The homestead gardens produce 110.86 Mg of fuelwood/year and 39.15 Mg of fodder/year which reduce the dependence on the natural forests. Thus by avoided deforestation and forest degradation in Cooch Block II there is netgain of247.06 Mg of CO2e annually. The monetary value o flive carbon offsets estimatedis US 1270.00 and average value ofcarbon credit per homegarden is Rs. US 28.22 with assumed value of 2.5USD per VER/CER in the present study annually. A cluster based approach by bundling together villages in the entire Cooch Behar-ll Block would result in approximately sequestering 2058051.8 ton CO2e andhence would claim US 5,145,129.5 per annum for maintaining and strengthening the ecosystem services from homestead gardens for livelihood sustenance.